Withering boundaries: Nile basin wetlands shrink as communities quest for life - CGIAR Research Program on Water, Land and Ecosystems (2016)
The project research teams and consortium members would like to acknowledge that the research leading to (This Report) was carried out under the CGIAR Research Program on Water, Land and Ecosystems in the Nile and East Africa Region with support from CGIAR Fund Donors. All the research activities under this project were carried out with funds under the project contract reference No. 4500025279. The CGIAR Research Program on Water, Land and Ecosystems (WLE) combines the resources of 11 CGIAR centers, the Food and Agriculture Organization of the United Nations (FAO) and numerous national, regional and international partners to provide an integrated approach to natural resource management research. WLE promotes a new approach to sustainable intensification in which a healthy functioning ecosystem is seen as a prerequisite to agricultural development, resilience of food systems and human well-being. This program is led by the International Water Management Institute (IWMI) and is supported by the CGIAR System Organization, a global research partnership for a food-secure future. https://wle.cgiar.org/research/regions/nile-and-east-africa The project partners also would like to express their sincere thanks towards Mr. Fredrick Mugira, a multiple award-winning water journalist and development communication specialist, who supported us in writing these articles.